2020
DOI: 10.1007/s13205-020-02498-6
|View full text |Cite
|
Sign up to set email alerts
|

Human microRNAs in host–parasite interaction: a review

Abstract: MicroRNAs (miRNAs) are a group of small noncoding RNA molecules with significant capacity to regulate the gene expression at the post-transcriptional level in a sequence-specific manner either through translation repression or mRNA degradation triggering a fine-tuning biological impact. They have been implicated in several processes, including cell growth and development, signal transduction, cell proliferation and differentiation, metabolism, apoptosis, inflammation, and immune response modulation. However, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 116 publications
(119 reference statements)
0
41
0
Order By: Relevance
“…MicroRNAs can be modulated by different pathogens, such as viruses, bacteria, and protozoan parasites ( Chandan et al., 2019 ; Acuna et al., 2020 ). Differential expression of diverse miRNA has been identified in Leishmania -host interaction in vitro and experimental in vivo systems with visceral and cutaneous strains of Leishmania ( Acuna et al., 2020 ) as well as human leishmaniasis ( Paul et al., 2020 ). Specifically, in cutaneous leishmaniasis caused by L. braziliensis miR-361-3p, a regulator of GZMB and tumor necrosis factor (TNF) was down-regulated and related to treatment failure ( Lago et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs can be modulated by different pathogens, such as viruses, bacteria, and protozoan parasites ( Chandan et al., 2019 ; Acuna et al., 2020 ). Differential expression of diverse miRNA has been identified in Leishmania -host interaction in vitro and experimental in vivo systems with visceral and cutaneous strains of Leishmania ( Acuna et al., 2020 ) as well as human leishmaniasis ( Paul et al., 2020 ). Specifically, in cutaneous leishmaniasis caused by L. braziliensis miR-361-3p, a regulator of GZMB and tumor necrosis factor (TNF) was down-regulated and related to treatment failure ( Lago et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Echinococcus granulosus infection in the host is a complex dynamic process, which involves the recognition and interaction of a variety of biological molecules, including genes [ 33 ], proteins [ 1 ], and miRNAs [ 42 ]. Upregulation or downregulation of molecular expression likely causes different individuals of the same host to have different resistance, similarly to reports about Plasmodium homocircumflexum [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis (also known as bilharzia) is a parasitic infectious disease caused by blood flukes of the Schistosoma genus and is one of the most prevalent zoonotic diseases worldwide [ 110 ]. Schistosoma mansoni (mainly found in Africa, South America, the Caribbean, and the Middle East), Schistosoma haematobium (Africa and the Middle East), and Schistosoma japonicum (China and southeast Asia) are the main causes of this human disease [ 111 ]. Schistosomes get into the body from human skin, and schistosome cercariae migrate to the liver via portal-mesenteric vein system.…”
Section: Micrornas and Immune Responses Against Parasitic Infectiomentioning
confidence: 99%
“…In addition, mmu-miR-223, mmu-miR-146a/b, mmu-miR-155, mmu-miR-34c, mmu-miR-199, and mmu-miR-134 exhibit peak expression levels during the late phase of infection and may symbolize the development of schistosomal hepatopathy [ 112 ]. The roles of miRNAs and the pathogenesis of hepatic fibrosis in schistosomiasis by both S. japonicum and S. mansoni were recently reported, which highlighted their roles in regulating antifibrotic and profibrotic mechanisms [ 111 ]. It was shown that miR-150-5p, miR-146b-5p, miR-143-3p, miR-199a-3p, miR-10a-5p, miR-4521, miR-31-5p, miR-222-3p, and miR-221-3p were upregulated, whereas miR-663b was downregulated.…”
Section: Micrornas and Immune Responses Against Parasitic Infectiomentioning
confidence: 99%